The Information Structures of by + V-Ing in Social Media’s Legal Texts - Johan Tobias Kristiano (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2021)
The structure of a sentence might be influenced by how information is intended to be delivered. In legal texts, how words are arranged is a crucial factor as it might affect how readers understand the messages in the texts. This study investigates the information structure of a prepositional phrase (PP) namely by + V-ing in social media’s legal texts. The data sources of this study were nine legal texts from five social media, namely Twitter, Facebook, Instagram, WhatsApp, and TikTok. The analysis process resulted in the findings that 43 % of the phrases were preposed and 57 % were in postverbal position. The study also found that every placement of the PP is able to present both given or new information, with introduction of new information dominates the use of the PP. Further, the research also observed several contexts in which the PP is employed. From the research, it is expected that the results could help readers in understanding information delivered in legal texts.